2021
DOI: 10.21608/ejchem.2021.106210.4886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hepatitis C management on glycemic control among Type 2 Diabetes Mellitus patients

Abstract: Background: HCV and DM are chronic diseases of high global prevalence. Many studies proved the association between Hepatitis C and DM in the last three decades and this consists of an interrelated association; moreover, HCV infection triggers Diabetes Mellitus, most probably type 2. Objective: To assess the possibility of the improvement of T2DM in patients with HCV when applying the new DAA HCV treatment in Egypt. Patients and Methods:The current study is a prospective cohort hospital-based study that aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…4 Recent research indicated that liver disease is the leading cause of death in Egypt, where mathematical models estimated a growth in the number of individuals with liver cirrhosis and liver cancer in the coming years. 4,5 Hepatitis C virus (HCV) and Hepatitis B virus (HBV) infections progress through three distinct phases. New infections (mostly asymptomatic but rarely symptomatic in the form of acute hepatitis) may progress into chronic infections (typically asymptomatic), which may develop into consequences such as cirrhosis and hepatocellular carcinoma (HCC) that result in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent research indicated that liver disease is the leading cause of death in Egypt, where mathematical models estimated a growth in the number of individuals with liver cirrhosis and liver cancer in the coming years. 4,5 Hepatitis C virus (HCV) and Hepatitis B virus (HBV) infections progress through three distinct phases. New infections (mostly asymptomatic but rarely symptomatic in the form of acute hepatitis) may progress into chronic infections (typically asymptomatic), which may develop into consequences such as cirrhosis and hepatocellular carcinoma (HCC) that result in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%